Congenital Brain Damage: Cognitive Development Correlates With Lesion and Electroencephalographic Features. (April 2013) - Riva, Daria; Franceschetti, Silvana; Erbetta, Alessandra; Baranello, Giovanni; Esposito, Silvia; Bulgheroni, Sara
The purpose of this study was to assess cognitive development in 26 children with congenital focal brain lesion and unilateral spastic cerebral palsy first diagnosed and followed up for rehabilitation at our institution. Mean intelligence quotients (IQs) were correlated not only to the different features of the cerebral lesions, but also to the different types of electroencephalographic abnormalities. We also examined individual scores. We found that about 70% of the children had values of Full-Scale, Verbal, and Performance IQs within the normal range. No differences were found between left and right injured children. Different Verbal IQ–Performance IQ profiles were observed. Larger lesions and some electroencephalographic features, mainly signal slowing/attenuation as signs of structural brain damage, were significantly associated with lower intellectual abilities. The role of other factors, including genetic and environmental background variability, as well as rehabilitative treatments, on cognitive sequelae in such patients was discussed.